Steps towards the hyperfine splitting measurement of the muonic hydrogen ground state: pulsed muon beam and detection system characterization. (12th May 2016) - Adamczak, A.; Baccolo, G.; Bakalov, D.; Baldazzi, G.; Bertoni, R.; Bonesini, M.; Bonvicini, V.; Campana, R.; Carbone, R.; Cervi, T.; Chignoli, F.; Clemenza, M.; et al.
Abstract: The high precision measurement of the hyperfine splitting of the muonic-hydrogen atom ground state with pulsed and intense muon beam requires careful technological choices both in the construction of a gas target and of the detectors. In June 2014, the pressurized gas target of the FAMU experiment was exposed to the low energy pulsed muon beam at the RIKEN RAL muon facility. The objectives of the test were the characterization of the target, the hodoscope and the X-ray detectors. The apparatus consisted of a beam hodoscope and X-rays detectors made with high purity Germanium and Lanthanum Bromide crystals. In this paper the experimental setup is described and the results of the detector characterization are presented.